Analysis of the Sensitivity of the SW-420 Vibration Sensor to Minor Mechanical Disturbances in the Safe Security System - Putri, Naila Cahaya; Tasmi; Teary, Muhammad Gald (Program Studi Teknologi Informasi, Fakultas Teknik, Universitas Udayana, 2025)
Abstract The security of assets in closed storage such as safes faces challenges in the form of illegal unit removal and physical manipulation. This study aimed to design and evaluate an anti-theft alarm system based on the Arduino Uno microcontroller with an SW-420 vibration sensor. The approach used was a laboratory experimental method focusing on testing the system's responsiveness to low-intensity mechanical interference or